Climate change, migration, and refugee as triggers risk of leprosy spread - Badrul Nurul Hisyam; Tantut Susanto (Faculty of Nursing, Universitas Hasanuddin, 2026)
One of the challenges in controlling leprosy is the displacement of people and refugees, which has the potential to accelerate the spread of the disease to areas that were previously free of it (Hooij & Geluk, 2021). Migration, especially that triggered by conflict, climate instability causing natural disasters, or economic pressures, often triggers mass displacement of people (World Health Organization, 2016). Refugees and migrants often must live in densely populated areas with poor sanitation conditions and very limited access to health services (Feizi et al., 2023). This situation creates an ideal environment for the spread of infectious diseases such as leprosy, where close and repeated interactions between sufferers and healthy individuals can increase the risk of transmission (Mahardita et al., 2019; Susanto, 2020). Overcrowding in refugee camps and limited health facilities make early detection and treatment of leprosy difficult, allowing the disease to spread undetected (Bulstra et al., 2021).